The bridge to Belle Island - Klassen, Julie, 1964- (Bethany House, a division of Baker Publishing Group, 2019)
"Evidence from a mysterious death takes Benjamin to an island on the Thames. There, Isabelle is trapped by fear and a recurring dream about a man's death. Or is it a memory? When a second death brings everyone under suspicion, she realizes her island sanctuary will never be the same"--